Impuestos moderados, según Ibn Jaldún - Eduardo Escartín González; Francisco Velasco Morente; Luis González-Abril (Medievalista)
Ibn Khaldun was an early exponent (XIV century) of the economic liberalism and he had a materialistic conception of history; hence he refers to the institutions in the area of economy and presents his economic thought, which we make it known by employing the methodological absolutism and extracting it directly from his Muqaddimah. We relate some of his ideas with other similar exposed in different periods, and we emphasize those that are still useful today. From his considerations we highlight economic development, currency circulation, wealth, free trade, and price. Ibn Khaldun is taking on higher relevance for the reason that his considerations still seem to describe current situations and his proposals could be implemented today to overcome the economic crisis, even though he did not mention technological innovations that were unthinkable at his time.